Innovative Strategies for Hearing Loss Treatment - Żuk, Krystian; Góral, Alicja; Duszyńska, Kamila; Dolepski, Karol; Czachajda, Michał (Quality in Sport, 2025)
Introduction: Hearing loss significantly impacts patients’ quality of life, making it an increasingly common issue, particularly among the elderly. Hearing loss is assessed based on the sound intensity threshold in decibels, ranging from mild (21–40 dB) to profound (above 90 dB). It is categorized into three types: conductive, sensorineural, and mixed. Various rehabilitation and treatment methods are applied depending on the type and degree of hearing impairment. The aim of this paper is to review the current state of knowledge regarding the existing methods for treating hearing loss. Materials and methods: A literature review covering studies from 2019 to 2024 was conducted, utilizing the PubMed and Google Scholar databases. Summary of current knowledge: There are various methods to enhance hearing, including hearing aids, cochlear implants, and bone-anchored devices, which improve audibility and speech comprehension. While these methods are effective, they do not fully address all challenges faced by individuals with hearing loss, such as clear hearing in noisy environments. These therapies are continuously improved through technological advancements, such as smartphone integration, increasing patient satisfaction. Promising prospects include gene therapy, which potentially repairs genetic defects causing congenital deafness, and cell-based therapies enabling the regeneration of damaged auditory cells. Future research on hearing protection focuses on antioxidant, anti-inflammatory, and gene-supporting drugs, employing nanotechnology to enhance therapy effectiveness. Conclusions: Modern hearing technologies and biological therapies offer increasingly advanced methods for hearing rehabilitation. Each discussed method has its specific advantages, limitations, and applications. Continued research in this field may significantly transform the future of hearing loss treatment.